Wound anastomosis nail with long-acting slow-release antibacterial function and preparation method of wound anastomosis nail
By pretreatment, alkaline heat treatment and antibacterial drug loading on titanium-based wound staples, combined with the coating technology of biocompatible materials, long-term sustained-release antibacterial function is achieved, solving the problems of poor antibacterial performance and short antibacterial time of traditional staples.
Patent Information
- Application Number
- CN202411642261.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-28
AI Technical Summary
After the traditional wound anastomosis nail is closed, bacterial infection is prone to occur around the damaged tissue, with poor antibacterial performance and short antibacterial time.
By pretreatment, alkaline heat treatment and antibacterial drug loading on titanium-based staples, an antibacterial drug coating is formed, and a protective coating is coated with good biocompatible materials to achieve long-term sustained release antibacterial function.
It significantly enhances the antibacterial effect of anastomosis staples, extends the release cycle of antibacterial drugs, and solves the problems of poor antibacterial performance and short antibacterial time of traditional anastomosis staples.
Smart Images

Figure CN119524219A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of staplers, and in particular relates to a wound stapler with long-acting sustained-release antibacterial function and a preparation method thereof. Background Art
[0002] Wound staplers are important medical devices used to close wounds and promote the healing of damaged tissues during surgical operations. They are increasingly used in modern surgical operations. Their versatility and efficiency make them an important tool in various surgeries. Staplers can effectively reduce trauma to patients, shorten operation time and hospitalization time, and have the advantages of less trauma and faster recovery. First, staplers can be introduced through tiny incisions, thereby reducing damage to the patient's normal tissues. Compared with traditional surgical methods, the use of staplers can reduce bleeding, reduce the risk of infection, reduce postoperative pain, and shorten recovery time. This technology is particularly suitable for the elderly or patients with poor physical fitness, which can significantly reduce surgical risks and improve the quality of life after surgery. Secondly, the use of staplers in surgery makes the surgical process simpler and more efficient. Doctors can perform tissue anastomosis more accurately, reduce surgical errors, and improve the success rate of surgery. At the same time, the use of staplers can also shorten the operation time and reduce the time patients spend on the operating table, thereby reducing the risk of anesthesia and complications.
[0003] The application of staplers is mainly divided into two forms: external skin suturing and internal tissue suturing. Skin suturing refers to the use of staplers to close external skin wounds, thereby accelerating healing and reducing the risk of infection. The use of skin staples requires that the wound edges are neat and suitable for operation. After the wound is aligned, staplers are used to quickly close it to achieve the purpose of reducing bleeding and promoting healing. In addition, wound staplers are also widely used in the suturing of internal tissues and organs such as gastrointestinal surgery and lung surgery. In these operations, staplers can quickly and firmly close the body tissues, reduce the operation time, and reduce the risk of postoperative complications. Especially for some operations that require complex reconstruction, such as gastrointestinal anastomosis, the use of staplers can ensure the tightness of the anastomosis and reduce the risk of postoperative leakage.
[0004] In recent years, the materials and designs of staples have been continuously innovated and improved, making them perform well in different types of surgeries. Although staples have advantages such as high efficiency and safety in surgery, they still have obvious defects and deficiencies in practical applications. For example, after the traditional wound staples close the wound, bacterial infection is very likely to occur around the damaged tissue, especially in the case of complex surgical environment and long surgical time. Bacterial infection will not only delay the tissue healing process, but also may cause serious postoperative complications. At present, the research on wound staples mainly takes the material of staples as the starting point, and only considers whether the wound staples are degraded in the human body (such as Chinese patent applications with publication numbers CN111012420A and CN118064764A), while ignoring the antibacterial function of suture materials. Although there are also wound staples with antibacterial effects (such as Chinese patent applications with publication numbers CN116475698A), the situation where long-term anastomosis is required is not considered at present, and there are problems such as limited antibacterial effect and short duration. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a wound stapler with long-acting sustained-release antibacterial function and a preparation method thereof, thereby solving the problems of poor antibacterial performance and short antibacterial time of traditional wound staplers.
[0006] In order to solve the above technical problems, the present invention is implemented through the following technical solutions:
[0007] A method for preparing a wound stapler with long-acting sustained-release antibacterial function comprises the following steps:
[0008] Step 1) manufacturing or selecting titanium-based staples as raw materials and pretreating them;
[0009] Step 2) performing alkaline heat treatment on the pretreated titanium-based staples to enhance the effective contact surface between the later antibacterial drugs and the titanium-based staples;
[0010] Step 3) uniformly loading one or more antibacterial drugs on the surface of the titanium-based staple after the alkali heat treatment, thereby forming an antibacterial drug coating;
[0011] Step 4) coating the antibacterial drug coating with a material having good biocompatibility to form a protective coating to prevent the antibacterial drug from falling off or degrading from the surface of the titanium-based stapler, thereby achieving the purpose of long-term sustained release;
[0012] Step 5) preparing a wound stapler with long-acting sustained-release antibacterial function.
[0013] Furthermore, in step 1), the pretreatment includes: firstly performing preliminary polishing and fine polishing to ensure that the surface of the titanium-based staple is smooth and has no obvious scratches, so as to increase the adhesion of the subsequent coating, and then performing ultrasonic cleaning and drying to ensure that the surface of the titanium-based staple is neat and smooth, and completely removing metal chips and impurities during the polishing process.
[0014] Furthermore, the cleaning solution used in the ultrasonic cleaning includes 99.9% acetone, 99.9% ethanol and distilled water, wherein the acetone is used to remove grease and organic pollutants on the surface of the titanium-based staples, the ethanol is used to further clean and disinfect the surface of the titanium-based staples, and the distilled water is used to finally rinse the surface of the titanium-based staples.
[0015] Furthermore, in step 2), the specific operation of the alkaline heat treatment is: immersing the treated titanium-based staple in a 4-8 mol / L NaOH solution, and sealing and heating it in a vacuum drying oven at 60-80°C for 24-48 hours. During the sealing and heating process, high-concentration NaOH is used to remove the oxide film on the surface of the titanium-based staple, and at the same time, the surface of the titanium-based staple becomes rough and forms a microporous structure, thereby increasing the effective contact area between the later antibacterial drugs and the titanium-based staples, so as to increase the drug loading rate and enhance the antibacterial effect.
[0016] Furthermore, in step 3), the method for loading the antimicrobial drug coating on the surface of the titanium-based staple is: soaking the titanium-based staple after alkaline heat treatment in one or more antimicrobial drug solutions for a certain period of time, and then air-drying, and repeating the soaking and air-drying several times to ensure that the antimicrobial drug fully penetrates the surface of the titanium-based staple and forms a uniform antimicrobial drug coating.
[0017] Furthermore, in step 3), the antibacterial drug is any one or more combinations of triclosan, tetracycline, erythromycin, gentamicin, vancomycin, and cephalosporin.
[0018] Furthermore, in step 4), the method of coating the protective coating on the surface of the antibacterial drug coating is: immersing the titanium-based staple loaded with the antibacterial drug coating in one or more solutions of materials with good biocompatibility for a certain period of time, and then air-drying to ensure that the materials with good biocompatibility form a protective coating on the antibacterial drug coating.
[0019] Furthermore, in step 4), the method of coating the protective coating on the surface of the antibacterial drug coating is: immersing the titanium-based staple loaded with the antibacterial drug coating in one or more solutions of materials with good biocompatibility for a certain period of time, then air-drying, and then irradiating it under an ultraviolet sterilization lamp for a certain period of time, and at the same time using glutaraldehyde for cross-linking treatment to ensure that the material with good biocompatibility forms a stable protective coating on the antibacterial drug coating.
[0020] Furthermore, in step 4), the material with good biocompatibility is any one or more combinations of polyurethane, polyethylene glycol, chitosan, polyurethane, silk fibroin, wool protein, and collagen.
[0021] A wound anastomotic staple with long-acting sustained-release antibacterial function prepared by the above-mentioned preparation method.
[0022] The beneficial effects of the present invention are:
[0023] The present invention essentially proposes a method for loading antibiotics onto wound staples to achieve long-term sustained-release antibacterial. Under the premise of not affecting the physical properties of the original titanium staples, the method processes 20-200 nanometer micropores on the surface of the wound staples through alkaline heat treatment to form a porous groove structure, and then loads the antibacterial coating onto the surface of the wound staples to achieve the long-term sustained-release antibacterial function of the staples, which has a long-term and stable antibacterial effect, thereby solving the problems of poor antibacterial performance and short antibacterial time of traditional wound staples. In addition, the method is simple and efficient, and has prospects for industrialization and clinical application.
[0024] The wound stapler machine preparation method with long-acting sustained-release antibacterial function of the present invention has the following specific advantages:
[0025] 1. Enhanced antibacterial effect: Alkaline heat treatment removes the oxide film on the surface of the stapler and increases the density of hydroxyl groups on its surface. This surface structure is conducive to the attachment and fixation of antibacterial agents, thereby enhancing the antibacterial effect.
[0026] 2. Long-lasting antibacterial performance: Alkaline heat treatment and coating technology are used to give the surface of the stapler good porosity, forming micropores and microgroove structures on its surface. These structures provide sufficient sites for drug loading, which can increase the effective loading amount of the antibacterial agent, and fix the antibacterial agent through the polymer coating to achieve a long-lasting sustained-release antibacterial function, thereby effectively improving the antibacterial performance of the stapler.
[0027] 3. Improve the drug release cycle: alkaline heat treatment is carried out in a high temperature and high concentration sodium hydroxide environment to increase the roughness and porosity of the titanium staple surface, thereby greatly increasing the drug loading and extending the drug release cycle. Subsequently, through layer-by-layer self-assembly composite drug coating technology, the effective release time of the drug is further extended to ensure continuous drug release and achieve a longer therapeutic effect.
[0028] 4. Multifunctional application: This preparation method is not only suitable for wound staples, but can also be extended to other medical devices that require long-acting sustained-release antibacterial functions, such as bone nails and bone plates, cardiovascular stents, dental implants, etc., to improve their antibacterial properties and reduce the risk of infection.
[0029] 5. Innovative process: This preparation method is suitable for industrial production. Through innovative alkaline heat treatment and coating technology, the surface microstructure is optimized and the antibacterial agent is effectively fixed, which is easy to apply on a large scale. This innovative method not only improves the preparation efficiency, but also significantly enhances the antibacterial effect and drug release performance of medical devices.
[0030] In summary, the wound stapler with long-acting sustained-release antibacterial function and the preparation method thereof proposed in the present invention have significant advantages in improving antibacterial performance and prolonging drug release cycle, and are applicable to a wide range of wound repair fields.
[0031] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. The specific implementation of the present invention is given in detail by the following embodiments and their accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of this application. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0033] Figure 1 The present invention shows the surface microscopic morphology changes of the wound staples with long-acting sustained-release antibacterial function and the raw materials after molding, alkali heat treatment and drug loading in Examples 1 and 2 of the present invention; wherein Figure a is the surface microscopic morphology after raw material molding, Figure b is the surface microscopic morphology after alkali heat treatment, and Figure c is the surface microscopic morphology after drug loading.
[0034] Figure 2 The figures are actual comparison diagrams of the wound staples with long-acting sustained-release antibacterial function before and after molding in Examples 1 and 2 of the present invention; Figure a is a physical diagram of the titanium wire raw material before molding, and Figure b is a physical diagram of the staple raw material after molding.
[0035] Figure 3 The diagram is a diagram of the alkaline thermal reaction mechanism of the wound staples with long-acting sustained-release antibacterial function in Examples 1 and 2 of the present invention in a high-concentration sodium hydroxide solution.
[0036] Figure 4 The figure is a surface microscopic morphology change diagram of the wound stapler with long-acting sustained-release antibacterial function after alkali heat treatment in Example 1 of the present invention; wherein Figure a is a surface microscopic morphology diagram of the stapler after alkali heat treatment (300 times), Figure b is a surface microscopic morphology diagram of the stapler after alkali heat treatment (15000 times), and Figure c is a surface microscopic morphology diagram of the stapler after alkali heat treatment (40000 times).
[0037] Figure 5 This is a diagram showing the antibacterial effect of the wound stapler with long-acting sustained-release antibacterial function on Escherichia coli and Staphylococcus aureus in Example 1 of the present invention;
[0038] Figure 6 This is a diagram showing the antibacterial effect of the wound stapler with long-acting sustained-release antibacterial function on Escherichia coli and Staphylococcus aureus in Example 2 of the present invention;
[0039] Figure 7 This is a curve diagram of the cumulative drug release rate of the wound stapler with long-acting sustained-release antibacterial function in Examples 1 and 2 of the present invention. DETAILED DESCRIPTION
[0040] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings so that the purpose, features and advantages of the invention can be more clearly understood. It should be understood that the embodiments shown in the accompanying drawings are not intended to limit the scope of the present invention, but are only intended to illustrate the essential spirit of the technical solution of the present invention.
[0041] In the following description, certain specific details are set forth for the purpose of illustrating various disclosed embodiments to provide a thorough understanding of the various disclosed embodiments. However, those skilled in the relevant art will recognize that the embodiments may be practiced without one or more of these specific details. In other cases, well-known devices, structures, and techniques associated with the present application may not be shown or described in detail to avoid unnecessarily obscuring the description of the embodiments.
[0042] Unless the context requires otherwise, throughout the specification and claims, the word "comprise" and variations such as "include" and "have" should be construed in an open, inclusive sense, ie, should be interpreted as "including, but not limited to."
[0043] References throughout the specification to "one embodiment" or "an embodiment" indicate that a particular feature, structure, or characteristic described in connection with the embodiment is included in at least one embodiment. Thus, the appearances of "in one embodiment" or "in an embodiment" in various places throughout the specification are not necessarily all referring to the same embodiment. Furthermore, the particular features, structures, or characteristics may be combined in any manner in one or more embodiments.
[0044] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. It should be noted that the term "or" is generally employed in its sense including "and / or" unless the context clearly dictates otherwise.
[0045] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0046] The present invention provides a method for preparing a wound stapler with a long-acting sustained-release antibacterial function, which specifically comprises the following steps:
[0047] Step 1) preparing or selecting titanium-based staples as raw materials and pretreating them.
[0048] The reason for choosing titanium-based staples is that titanium (Ti) metal has excellent mechanical strength and ductility. Moreover, compared with magnesium (Mg)-based staples that produce hydrogen in the body, causing rapid corrosion and eventually causing the staples to fail, titanium-based (Ti) staples have excellent corrosion resistance and are not prone to chemical reactions or degradation in the body, ensuring the long-term stability of the staples in the body and the long-term tissue support effect. In addition, compared with other metals, titanium (Ti) metal is less toxic and has good biocompatibility.
[0049] The pretreatment includes: firstly, preliminary polishing and fine polishing are performed to ensure that the surface of the titanium-based staple is smooth and has no obvious scratches, so as to increase the adhesion of the subsequent coating, and then ultrasonic cleaning is performed for 15 to 20 minutes and drying is performed at 45° C. to ensure that the surface of the titanium-based staple is neat and smooth, and metal chips and impurities in the polishing process are completely removed.
[0050] The cleaning solution used in the ultrasonic cleaning includes 99.9% acetone, 99.9% ethanol and distilled water, wherein the acetone is used to remove grease and organic pollutants on the surface of the titanium-based staples, the ethanol is used to further clean and disinfect the surface of the titanium-based staples, and the distilled water is used to finally rinse the surface of the titanium-based staples.
[0051] Step 2) performing alkaline heat treatment on the pretreated titanium-based staples to enhance the effective contact surface between the subsequent antibacterial drugs and the titanium-based staples.
[0052] The specific operation of the alkali heat treatment is: immerse the treated titanium-based anastomotic staples in a 4-8 mol / L NaOH solution, and seal and heat them in a vacuum drying oven at 60-80° C. for 24-48 hours, and then take them out.
[0053] Under high temperature conditions, high-concentration NaOH is used to remove the oxide film on the surface of the titanium-based staples, and at the same time, the surface of the titanium-based staples becomes rough and forms a microporous structure, thereby increasing the effective contact area between the antibacterial drug and the titanium-based staples, thereby increasing the drug loading rate and enhancing the antibacterial effect.
[0054] After alkaline heat treatment, the number of hydroxyl groups (Ti-OH) on the surface of the titanium-based staples increases significantly, and about 80% of the active sites on the surface may form hydroxyl (Ti-OH) bonds. This surface modification not only improves the drug loading capacity of the titanium-based staples, but also significantly enhances the antibacterial properties of the titanium-based staples.
[0055] Step 3) uniformly loading one or more antibacterial drugs on the surface of the titanium-based staple after the alkali heat treatment, thereby forming an antibacterial drug coating.
[0056] The method for forming the antimicrobial drug coating is as follows: immersing the titanium-based staples that have been subjected to alkali heat treatment in one or more antimicrobial drug solutions for 15 to 30 seconds, then naturally air-drying them, and repeating the immersion and air-drying steps several times to ensure that the antimicrobial drugs fully penetrate the surface of the titanium-based staples and form a uniform antimicrobial drug coating.
[0057] The antibacterial drug of the present invention adopts any one or more combinations of broad-spectrum antibacterial agents such as triclosan, tetracycline, erythromycin, gentamicin, vancomycin, cephalosporin, etc. as loaded drugs.
[0058] Step 4) The antimicrobial drug coating is coated with a material having good biocompatibility to form a protective coating to prevent the antimicrobial drug from falling off or degrading from the surface of the titanium-based stapler, thereby achieving the purpose of long-term sustained release.
[0059] The method for forming the protective coating is: immersing the titanium-based staple loaded with the antibacterial drug coating in one or more materials with good biocompatibility for 15 to 20 seconds, and then naturally air-drying to ensure that the material with good biocompatibility forms a protective coating on the antibacterial drug coating.
[0060] Alternatively, the titanium-based stapler loaded with the antibacterial drug coating is immersed in a biocompatible material composed of any one or more combinations of polyurethane, polyethylene glycol, chitosan, polyurethane, silk fibroin, wool protein, collagen, etc. for 15 to 20 seconds, then naturally air-dried, and then irradiated under an ultraviolet sterilization lamp for a certain period of time, and cross-linked with glutaraldehyde to ensure that the biocompatible material forms a stable protective coating on the antibacterial drug coating.
[0061] The material with good biocompatibility of the present invention adopts any one or more combinations of polyurethane, polyethylene glycol, chitosan, polyurethane, silk fibroin, wool protein, collagen, etc., and can cover the above-mentioned antibacterial drug coating therein to form a layer-by-layer self-assembly structure, so that the antibacterial drug can be stably loaded onto the titanium-based stapler, thereby achieving slow release of the antibacterial agent, prolonging the action time of the antibacterial drug, and reducing the risk of bacterial infection at the wound.
[0062] Step 5) preparing a wound stapler with long-acting sustained-release antibacterial function.
[0063] The present invention also provides a wound stapler with a long-acting sustained-release antibacterial function prepared by the above-mentioned preparation method. In the case of a wound that requires long-term suturing, the stapler of the present invention can provide stable and long-lasting mechanical support for wound suturing due to its stable material and difficulty in degradation. At the same time, the design of the composite coating structure (titanium oxide porous layer, antibacterial coating and polyurethane coating) enables the stapler to provide a long-lasting drug release effect, thereby effectively preventing infection, promoting healing, and improving the patient's postoperative recovery quality.
[0064] Two preferred embodiments of the present invention are described in detail below.
[0065] Example 1
[0066] Step 1) Ti-based wound staplers (or Ti metal wires) are selected and polished in steps using silicon carbide sandpaper with a roughness of 400 to 1500 meshes. First, 400-mesh sandpaper is used for preliminary polishing, and then finer sandpaper (such as 600 mesh, 800 mesh, 1000 mesh, 1200 mesh, and 1500 mesh) is gradually used for fine polishing to ensure that the surface is smooth and has no obvious scratches.
[0067] Then, ultrasonic cleaning was performed in an ultrasonic cleaner using 99.9% acetone, 99.9% ethanol, and distilled water, respectively, for 15 minutes each time. Acetone was used to remove grease and organic contaminants, ethanol was used for further cleaning and disinfection, and distilled water was used for final rinsing. After cleaning, the staples were dried at 45°C to ensure that the surface of the Ti-based wound staplers was neat and smooth, and to completely remove metal chips and impurities generated during the polishing process.
[0068] See also Figure 2 As shown, Figure 2 Figure a is a physical picture of the titanium wire raw material before forming, and Figure b is a physical picture of the staple raw material after forming. It can be seen that the staple raw material processed from the titanium wire is U-shaped and has a smooth surface.
[0069] Step 2) The polished, cleaned and dried Ti-based wound staplers were immersed in a 4M NaOH solution and sealed and heated in a vacuum drying oven at 60°C for 24 hours. This step is used to form an oxide layer on the metal surface to improve the adhesion of subsequent coatings. After treatment, the sample was rinsed with deionized water to ensure that the residual NaOH solution was completely removed.
[0070] See also Figure 3 As shown, this embodiment uses the strong alkalinity of NaOH to treat the oxide film on the surface of the Ti-based wound stapler, thereby forming a larger porosity and surface area. In an alkaline environment, NaOH can effectively corrode the oxide film and generate hydroxyl groups (Ti-OH) on the Ti surface through the following chemical reaction:
[0071] Ti+NaOH+H2O→Ti-OH+Na + +OH - ;
[0072] This chemical reaction not only increases the roughness and porosity of the surface of Ti-based wound staples, but also provides chemical binding points for subsequent drug loading. The drug molecules form a strong chemical bond with the surface of Ti-based wound staples through hydroxyl groups, thereby achieving effective fixation and sustained release of the drug. Through alkaline heat treatment, the surface of Ti-based wound staples forms a structure with high porosity and large surface area, providing ideal conditions for efficient loading and uniform distribution of drugs.
[0073] Step 3) The Ti-based wound stapler after alkali heat treatment was immersed in a 10 mg / mL triclosan ethanol solution for 15 seconds, and then placed in a fume hood to air dry naturally. Next, the sample was immersed in a solution containing 2% chitosan for 30 seconds, and then air-dried in a fume hood, and the above immersion and air-drying steps were repeated three times to ensure that the drug fully penetrated and formed a uniform coating.
[0074] See also Figure 1As shown, after drug loading, the pore structure on the surface of the stapler is filled with antibacterial drugs, and the surface becomes relatively flat. The drugs are evenly distributed inside the pores, so that the entire surface presents a continuous smooth state. The flat structure after drug loading helps to ensure the uniform release of the drug. Since the drugs are filled into the pores, the drugs are gradually dissolved in the human body environment, so that the drugs can achieve a sustained release effect. This can not only avoid the toxic and side effects caused by the sudden release of drugs (that is, the drug is released in large quantities in a short period of time), but also avoid the problem of insufficient local drug concentration, ensuring that the antibacterial drugs exert their antibacterial effects in the wound for a long time and stably, thereby reducing the risk of infection and promoting wound healing. Uniform drug distribution is also beneficial to the structural stability of the staples under stress conditions, avoiding changes in mechanical properties caused by local concentration differences.
[0075] Step 4) Prepare a polyurethane solution with a mass fraction of 30%, soak the drug-loaded Ti-based wound staples in the polyurethane solution for 15 seconds, take them out and place them in a fume hood to air dry naturally. The coated sample is placed under an ultraviolet sterilization lamp for 15 minutes, and cross-linked with glutaraldehyde. This step enhances the stability of the coating and ensures the durability and sustained release effect in the in vivo environment.
[0076] The wound stapler raw material and the wound stapler loaded with drugs used in this embodiment were tested for antibacterial activity against Escherichia coli and Staphylococcus aureus. Figure 5 As shown, the inhibition zone of the wound stapler loaded with medicine in this embodiment against Escherichia coli and Staphylococcus aureus is much larger than 1 mm, and the antibacterial effect is significant.
[0077] Example 2
[0078] Step 1) Ti-based wound staplers (or Ti metal wires) are selected and polished in steps using silicon carbide sandpaper with a roughness of 400 to 1500 meshes. First, 600-mesh sandpaper is used for preliminary polishing, and then finer sandpaper (such as 800 mesh, 1200 mesh, 1500 mesh and 2000 mesh) is gradually used for fine polishing to ensure that the surface is smooth and has no obvious scratches, so as to increase the adhesion of the subsequent coating.
[0079] Then, the Ti-based wound staplers were cleaned in an ultrasonic cleaner using 99.9% acetone, 99.9% ethanol, and deionized water, respectively, for 20 minutes each time to thoroughly remove grease, organic matter, and metal shavings and impurities generated during polishing. Acetone was used to remove grease and organic contaminants, ethanol was used for further cleaning and disinfection, and distilled water was used for final rinsing. After cleaning, the staplers were dried at 45°C to ensure that the surface of the Ti-based wound staplers was neat and smooth, and to thoroughly remove metal shavings and impurities generated during polishing.
[0080] See also Figure 2 As shown, Figure 2Figure a is a physical picture of the titanium wire raw material before forming, and Figure b is a physical picture of the staple raw material after forming. It can be seen that the staple raw material processed from the titanium wire is U-shaped and has a smooth surface.
[0081] Step 2) The polished, cleaned and dried Ti-based wound staplers were immersed in a NaOH solution with a concentration of 8M and sealed and heated in a vacuum drying oven at 80°C for 48 hours. This step is used to form an oxide layer on the metal surface to improve the adhesion of subsequent coatings. After treatment, the sample was rinsed with deionized water to ensure that the residual NaOH solution was completely removed.
[0082] See also Figure 3 As shown, this embodiment uses the strong alkalinity of NaOH to treat the oxide film on the surface of the Ti-based wound stapler, thereby forming a larger porosity and surface area. In an alkaline environment, NaOH can effectively corrode the oxide film and generate hydroxyl groups (Ti-OH) on the Ti surface through the following chemical reaction:
[0083] Ti+NaOH+H2O→Ti-OH+Na + +OH - ;
[0084] This chemical reaction not only increases the roughness and porosity of the surface of Ti-based wound staples, but also provides chemical binding points for subsequent drug loading. The drug molecules form a strong chemical bond with the surface of Ti-based wound staples through hydroxyl groups, thereby achieving effective fixation and sustained release of the drug. Through alkaline heat treatment, the surface of Ti-based wound staples forms a structure with high porosity and large surface area, providing ideal conditions for efficient loading and uniform distribution of drugs.
[0085] Step 3) Soak the Ti-based wound stapler after alkali heat treatment in a solution containing tetracycline (concentration of 25 mg / mL) for 30 seconds, and then air-dry it in a fume hood. Repeat the soaking and air-drying steps three times to allow the antibiotic to penetrate and evenly distribute on the surface of the Ti-based wound stapler.
[0086] Step 4) Soaking the Ti-based wound stapler coated with the drug in a 1% chitosan solution for 20 seconds to form an antibacterial protective coating.
[0087] The wound stapler raw material and the wound stapler loaded with drugs used in this embodiment were tested for antibacterial activity against Escherichia coli and Staphylococcus aureus. Figure 6 As shown in the figure, the inhibition zone of the wound staples loaded with drugs in this embodiment against Escherichia coli and Staphylococcus aureus is much larger than 1 mm, and the antibacterial effect is significant. The wound staples loaded with drugs in Examples 1 and 2 were tested for the cumulative drug release rate. Figure 7As shown, the cumulative drug release rate of the drug-loaded staples in Examples 1 and 2 reached 78% within the first 48 hours, but the subsequent drug release rate gradually slowed down, and the drug was still being released until 230 hours. The polyurethane coating delayed the drug release and achieved long-term sustained release of the antibacterial staples, which was beneficial to enhance the antibacterial effect to cope with long-term wound healing.
[0088] Example 3
[0089] Step 1) Ti-based wound staplers (or Ti metal wires) are first polished in steps using silicon carbide sandpaper with a roughness of 400 to 1500 mesh. Initial polishing is performed using 600-mesh sandpaper, followed by finer sandpaper (800 mesh, 1200 mesh, 1500 mesh, and 2000 mesh) to ensure a smooth surface without obvious scratches and to increase the adhesion of subsequent coatings.
[0090] Then, use 99.9% acetone, 99.9% ethanol and deionized water to clean in an ultrasonic cleaner, each cleaning for 20 minutes to thoroughly remove impurities such as grease, organic matter and metal chips. Acetone is used to remove grease and organic pollutants, ethanol is used for further cleaning and disinfection, and deionized water is used for final rinsing. After cleaning, dry at 45°C to ensure that the surface of the Ti-based wound stapler is smooth and free of residue.
[0091] See also Figure 1 As shown, Figure 1 Figure a is a physical picture of the titanium wire raw material before forming, and Figure b is a physical picture of the staple raw material after forming. It can be seen that the staple raw material processed from the titanium wire is U-shaped and has a smooth surface.
[0092] Step 2) The polished and cleaned Ti-based staples were immersed in 8M NaOH solution and sealed and heated in a vacuum oven at 80°C for 48 hours. This step uses the strong alkalinity of NaOH to remove the oxide film on the surface of the staples and form surface micropores and hydroxyl (Ti-OH) binding points, thereby increasing the antimicrobial loading. The treated surface of the titanium-based staples obtained a surface with high porosity and rough structure, which helps to improve the uniform coverage and adhesion of the drug. After treatment, the sample was rinsed with deionized water to ensure that the residual NaOH solution was completely removed.
[0093] See also Figure 3 As shown, this embodiment uses the strong alkalinity of NaOH to treat the oxide film on the surface of the Ti-based wound stapler, thereby forming a larger porosity and surface area. In an alkaline environment, NaOH can effectively corrode the oxide film and generate hydroxyl groups (Ti-OH) on the Ti surface through the following chemical reaction:
[0094] Ti+NaOH+H2O→Ti-OH+Na ++OH - ;
[0095] This chemical reaction not only increases the roughness and porosity of the surface of Ti-based wound staples, but also provides chemical binding points for subsequent drug loading. The drug molecules form a strong chemical bond with the surface of Ti-based wound staples through hydroxyl groups, thereby achieving effective fixation and sustained release of the drug. Through alkaline heat treatment, the surface of Ti-based wound staples forms a structure with high porosity and large surface area, providing ideal conditions for efficient loading and uniform distribution of drugs.
[0096] Step 3) The titanium-based staples after alkali heat treatment were immersed in a 50 μg / mL solution of nanosilver particles (AgNPs) for 20 minutes to provide preliminary antibacterial protection with the nanosilver particles. Subsequently, the sample was placed in a composite solution of penicillin and 1% chitosan at a concentration of 20 mg / mL, immersed for 15 seconds each time and air-dried, and this step was repeated three times. The chitosan and penicillin composite coating provides long-lasting antibacterial and sustained-release functions for the wound staples.
[0097] Step 4) Soak the drug-loaded titanium-based stapler in a 3% polyethylene glycol (PEG) solution and air-dry under natural conditions. The PEG coating has good hydrophilicity, which is conducive to the sustained release and biocompatibility of the drug. To enhance the protective effect, a 2% polylactic acid (PLA) solution is applied to form an outer degradation protective film. This coating provides long-term support for sustained release of the drug and ensures biological stability in the in vivo environment. The wound stapler raw material and the drug-loaded wound stapler used in this embodiment were tested for antibacterial effects against Escherichia coli and Staphylococcus aureus, respectively.
[0098] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a wound stapler with long-acting sustained-release antibacterial function, characterized in that: The following steps are involved: Step 1) manufacturing or selecting titanium-based staples as raw materials and pretreating them; Step 2) performing alkaline heat treatment on the pretreated titanium-based staples to enhance the effective contact surface between the later antibacterial drugs and the titanium-based staples; Step 3) uniformly loading one or more antibacterial drugs on the surface of the titanium-based staple after the alkali heat treatment, thereby forming an antibacterial drug coating; Step 4) coating the antibacterial drug coating with a material having good biocompatibility to form a protective coating to prevent the antibacterial drug from falling off or degrading from the surface of the titanium-based stapler, thereby achieving the purpose of long-term sustained release; Step 5) preparing a wound stapler with long-acting sustained-release antibacterial function.
2. The preparation method according to claim 1, characterized in that: In step 1), the pretreatment includes: firstly performing preliminary polishing and fine polishing to ensure that the surface of the titanium-based staple is smooth and has no obvious scratches, so as to increase the adhesion of the subsequent coating, and then performing ultrasonic cleaning and drying to ensure that the surface of the titanium-based staple is neat and smooth, and completely removing metal chips and impurities during the polishing process.
3. The preparation method according to claim 2, characterized in that: The cleaning solution used in the ultrasonic cleaning includes 99.9% acetone, 99.9% ethanol and distilled water, wherein the acetone is used to remove grease and organic pollutants on the surface of the titanium-based staples, the ethanol is used to further clean and disinfect the surface of the titanium-based staples, and the distilled water is used to finally rinse the surface of the titanium-based staples.
4. The preparation method according to claim 1, characterized in that: In step 2), the specific operation of the alkaline heat treatment is: immersing the treated titanium-based staple in a 4-8 mol / L NaOH solution, and sealing and heating it in a vacuum drying oven at 60-80°C for 24-48 hours. During the sealing and heating process, high-concentration NaOH is used to remove the oxide film on the surface of the titanium-based staple, and at the same time, the surface of the titanium-based staple becomes rough and forms a microporous structure, thereby increasing the effective contact area between the later antibacterial drugs and the titanium-based staples, so as to increase the drug loading rate and enhance the antibacterial effect.
5. The preparation method according to claim 1, characterized in that: In step 3), the method for loading the antimicrobial drug coating on the surface of the titanium-based staple is: soaking the titanium-based staple after alkaline heat treatment in one or more antimicrobial drug solutions for a certain period of time, and then air-drying, and repeating the soaking and air-drying several times to ensure that the antimicrobial drug fully penetrates the surface of the titanium-based staple and forms a uniform antimicrobial drug coating.
6. The preparation method according to claim 1, characterized in that: In step 3), the antibacterial drug is any one or more combinations of triclosan, tetracycline, erythromycin, gentamicin, vancomycin, and cephalosporin.
7. The preparation method according to claim 1, characterized in that: In step 4), the method of coating the protective coating on the surface of the antibacterial drug coating is: immersing the titanium-based staple loaded with the antibacterial drug coating in one or more solutions of materials with good biocompatibility for a certain period of time, and then air-drying to ensure that the materials with good biocompatibility form a protective coating on the antibacterial drug coating.
8. The preparation method according to claim 1, characterized in that: In step 4), the method of coating the protective coating on the surface of the antibacterial drug coating is: immersing the titanium-based staple loaded with the antibacterial drug coating in one or more solutions of materials with good biocompatibility for a certain period of time, then air-drying, and then irradiating it under an ultraviolet sterilization lamp for a certain period of time, and at the same time using glutaraldehyde for cross-linking treatment to ensure that the material with good biocompatibility forms a stable protective coating on the antibacterial drug coating.
9. The preparation method according to claim 1, characterized in that: In step 4), the material with good biocompatibility is any one or more combinations of polyurethane, polyethylene glycol, chitosan, polyurethane, silk fibroin, wool protein, and collagen.
10. A wound anastomotic staple with long-acting sustained-release antibacterial function prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method and applications of antibacterial and biodegradable zinc alloy anastomosis nail
CN111012420A
Drug-loaded anastomosis nail processing technology
CN116475698A
High-toughness degradable medical zinc-lithium-magnesium-yttrium-niobium alloy wire and anastomosis nail made of same
CN118064764A